Scotland's referendum and the media : national and international perspectives - Blain, Neil, 1951-; Hutchison, David, 1944 September 24-; Hassan, Gerry (Edinburgh : Edinburgh University Press, 2016)
This collection of essays explores how the 2014 Scottish referendum was presented in the media not only in Scotland but elsewhere in the United Kingdom, in Europe and beyond.
Scotland's Referendum and the Media -- Copyright -- Contents -- Preface -- Part One The Referendum in Scotland -- 1 The Unexpected Campaign -- 2 The Media Landscape In Scotland -- 3 Broadcasting and the Press: Some Key Moments -- 4 Scotland's Changing 'Community of the Communicators': The Political Commentariat and the Independence Referendum -- 5 The Scottish Press Account: Narratives of the Independence Referendum and its Aftermath -- 6 Scottish TV Coverage of the Referendum Campaign from September 2012 to September 2014 -- 7 'Liked', 'Shared', Re-tweeted: The Referendum Campaign on Social Media -- 8 Sport, Gender and National Identities -- Part Two Views from the UK -- 9 English Television News Coverage of the Scottish Referendum -- 10 The English Press and the Referendum -- 11 Wales, Devolution and the Scottish Independence Debate -- 12 Our Friends Across the Water: Northern Ireland Media Coverage of the Scottish Independence Referndum -- Part Three International Perspectives -- 13 'Knock-on Consequences': Irish Media Coverage of the Scottish Referendum -- 14 Spain, Catalonia and the Scottish Referendum: A Study in Multiple Realities -- 15 The French View -- 16 The Scottish Referendum in Austrian, German and Swiss Media -- 17 The Scottish Referendum: the View from Quebec -- 18 The Scotland Referendum in the English-language Canadian Media -- 19 Australia and the Scottish Independence Referendum -- 20 Afterword: Reimagining Scotland in a New Political Landscape -- Notes on the Contributors -- Index.
Includes bibliographical references and index.
Online resource; title from PDF title page (JSTOR, viewed April 25, 2019).
JSTOR
Keywords: Mass media -- Political aspects -- Scotland; Referendum -- Scotland; Self-determination, National -- Scotland -- History -- 21st century; Référendum -- Écosse.; Droit des peuples à disposer d'eux-mêmes -- Écosse -- Histoire -- 21e siècle.; PSYCHOLOGY -- Social Psychology; Mass media -- Political aspects; Referendum; Self-determination, National; Scotland; 2000-2099; Electronic books; History